2022
DOI: 10.3389/fmicb.2022.919725
|View full text |Cite
|
Sign up to set email alerts
|

The Future of Synbiotics: Rational Formulation and Design

Abstract: Synbiotics, mixtures of live microbes and substrates selectively utilized by host organisms, are of considerable interest due to their ability to improve gastrointestinal health. However, formulating synbiotics remains challenging, due in part, to the absence of rational strategies to assess these products for synbiotic activities prior to clinical trials. Currently, synbiotics are formulated as either complementary or synergistic. Complementary synbiotics are made by combining probiotics and prebiotics, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 70 publications
0
9
0
1
Order By: Relevance
“…A properly constructed synergistic synbiotic can likewise prove to be an effective way to turn non-responders into responders, and therefore, foster the efficacy of therapy across a wider client base while enhancing therapy success rates. As shown in Figure 4, a synergistic synbiotic is a combination of probiotics and prebiotics that work together to improve the health of the gut microbiome [284]. This can lead to improved digestion, better nutrient absorption, and reduced inflammation, all of which can help the body better respond to therapies.…”
Section: Synbioticsmentioning
confidence: 99%
“…A properly constructed synergistic synbiotic can likewise prove to be an effective way to turn non-responders into responders, and therefore, foster the efficacy of therapy across a wider client base while enhancing therapy success rates. As shown in Figure 4, a synergistic synbiotic is a combination of probiotics and prebiotics that work together to improve the health of the gut microbiome [284]. This can lead to improved digestion, better nutrient absorption, and reduced inflammation, all of which can help the body better respond to therapies.…”
Section: Synbioticsmentioning
confidence: 99%
“…Notably, at the intervention doses presented in this study, an increase in tight junction protein expression was also observed in the MOS or VL8 groups, and the difference in gut barrier repair effect between the three treatment groups was not statistically significant. Therefore, the product meets the definition of a complementary synbiotic, but not a synergistic synbiotic, according to the consensus statement published by International Scientific Association for Probiotics and Prebiotics (ISAPP). , …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the product meets the definition of a complementary synbiotic, but not a synergistic synbiotic, according to the consensus statement published by International Scientific Association for Probiotics and Prebiotics (ISAPP). 46,47 In clinical reports, complementary synbiotics, when used as alternative or complementary therapies for patients with UC, have been shown to provide benefits by decreasing the levels of pro-inflammatory cytokines associated with the pathophysiology of UC, mainly through activation of gut microbial metabolism and increasing the abundance of beneficial bacteria. 24,48 In this study, the abundance of the genus Lactobacillus, particularly L. murinus and L. reuteri, has significantly increased in the SYN group.…”
Section: Cohousing Of Synbiotics-dosed Mice Alters Gut Microbiota Com...mentioning
confidence: 99%
“…The future of synbiotics relies on a methodical formulation and design process. This involves the careful selection of synbiotics that harmonize and enhance each other's effects, guided by their specific mechanisms of action and the intended health benefits [ 65 ].…”
Section: The Effect Of Prebiotics Probiotics and Synbiotics In Ibdmentioning
confidence: 99%